Aligning the planning, development, and implementation of complex interventions to local contexts with an equity focus: application of the PRISM/RE-AIM Framework - Monica Pérez Jolles; Meredith P. Fort; Russell E. Glasgow (International Journal for Equity in Health, 2024)
Abstract For the fields of implementation science and health equity, understanding and being responsive to local contexts is of utmost importance to better inform the development, implementation, and evaluation of healthcare and public health interventions to increase their uptake and sustainment. Contexts are multi-level and include political, historical, economic, and social factors that influence health, as well as organizational characteristics, reflecting the richness of members’ views, resources, values, and needs. Poor alignment between solutions and those contextual characteristics could have an impact on inequities. The PRISM (Practical Robust Implementation and Sustainability Model) is a context-based implementation science framework that incorporates RE-AIM outcomes (Reach, Effectiveness, Adoption, Implementation, Maintenance) and offers guidance to researchers, practitioners, and their patient and community partners on how to conceptualize, assess, and address contextual domains with a focus on health equity. Drawing from systems thinking, participatory engagement, and health equity principles, this commentary expands on previous work to 1) offer a novel perspective on how to align an intervention’s core functions and forms with the PRISM’s contextual domains, and 2) foster an ongoing and iterative engagement process with diverse partners throughout the research and practice process using a co-creation approach. We recommend intervention-to-context alignment through iterative cycles. To that end, we present the RE-AIM Framework’s ‘outcomes cascade’ to illustrate touch points of opportunity and gaps within and across each of the five RE-AIM outcomes to illustrate ‘where things go wrong’. We present a case study to illustrate and offer recommendations for research and practice efforts to increase contextual responsiveness, and enhance alignment with context before, during, and after implementation efforts and to ensure equity is being addressed. We strive to make a conceptual contribution to advance the field of pragmatic research and implementation of evidence-based practices through the application of the contextually-based PRISM framework with a focus on health equity.